Review of techniques for identification of underground bord and pillar workings - Govender, Ganasen Loganathan (My University, 2018)
The higher quality virgin coal resources in the Witbank Coalfield are near completion, hence new methods of mining the underground coal pillars that have been left insitu as primary support becomes attractive to mine using opencast methods. Up until 2006 more than three million pillars have been created (van der Merwe, 2006) and have been growing since. There are various challenges associated with pillar extraction via opencast mining method. These challenges relate to spontaneous combustion, underground water and the exact spatial location of underground pillars that have been mined in the early to mid-1900. The reliability of old underground mine plans pre-1960, before the Coalbrook disaster, saw underground pillars not being offset which resulted in unreliable survey plans (van der Merwe, 2006). This report focuses on possible techniques that can be used to identify underground pillars where no water and no spontaneous combustion are evident. The following two methods have been tested: Ground Penetrating Radar (GPR) technique which is based on geophysics and a down the hole 3D laser method using the Cavity, Auto-scanning, Laser System (CALS Tool) which uses reflectorless principles to measure the geometries of the underground pillars. The GPR did not provide any conclusive data, whilst the CALS Tool provides detailed information of the workings. The CALS Tool is not practical to identify every single pillar in a reserve but can be used on a larger extent as a short term mine planning mechanism. The CALS Tool proved to have the ability to identify the spatial location of the underground workings as confirmed by the test done at TOC.
A research report submitted to the Faculty of Engineering and Built Environment, University of the Witwatersrand, Johannesburg, in the partial fulfilment of the requirements for the degree of Master of Science in Engineering, January 2018
Keywords: Ground control (Mining); Pillaring (Mining)